2021
DOI: 10.1590/s1984-29612021073
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission and kinetic of antibodies anti-Neospora caninum in naturally infected lambs in the semiarid region of Brazil

Abstract: Aimed with this study to evaluate vertical transmission of Neospora caninum in naturally infected sheep and to monitor the kinetics of antibodies against this protozoon in their lambs. Therefore, 48 pregnant ewes, from five herds, were divided into two groups: G1 - positive for anti-N. caninum antibodies, with 19 animals; and G2 - seronegative, with 29 animals. Blood samples were taken from the ewes and their lambs, immediately after birth, before ingesting colostrum, and 2, 7, 14, 21, 28, 35, 42, 49 and 56 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Similarly, a 93% endogenous transplacental transmission rate was described in another sheep flock in Spain [8]. As in previous studies carried out in cattle and sheep [45][46][47], we also found that seropositive sheep with high antibody titres were more likely to have seropositive offspring. Thus, individual N. caninum-specific antibody levels can also be used as a predictive tool for identifying animals with a high risk of endogenous transplacental transmission.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, a 93% endogenous transplacental transmission rate was described in another sheep flock in Spain [8]. As in previous studies carried out in cattle and sheep [45][46][47], we also found that seropositive sheep with high antibody titres were more likely to have seropositive offspring. Thus, individual N. caninum-specific antibody levels can also be used as a predictive tool for identifying animals with a high risk of endogenous transplacental transmission.…”
Section: Discussionsupporting
confidence: 89%
“…As in cattle, endogenous transplacental transmission (due to reactivation of latent N. caninum infections during pregnancy) has been found to be highly successful in sheep (96.6% of gestations) [9] and in goats (71.4-100% vertical transmission rate) [42,43]. However, other studies in sheep described low vertical transmission rates (15-31%) without associated abortions [44,45]. In this flock, endogenous transplacental transmission was the main route of parasite transmission since 86.5% of the offspring born from N. caninum seropositive sheep were seropositive.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of a high rate of endogenous vertical transmission in naturally infected sheep (6/ 19 -31.6%) was observed in the semi-arid region of the state of Paraíba, Brazil, in which chronically infected females gave birth to clinically healthy animals, but infected and with potential for transmissibility to future offspring or to the definitive host (Feitosa et al, 2021). Vertical transmission seems to be of greater importance in the perpetuation of the parasite in small ruminants when compared to horizontal transmission, since the same female can transmit the protozoan to several subsequent generations, making the occurrence and maintenance of the disease in the herd possible even in the absence of the definitive host (Pereira et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Reactivation of chronic N. caninum infection during pregnancy and endogenous transplacental transmission of the parasite to the offspring is known to be a common event in cattle, but the information on the efficiency of vertical transmission in small ruminants is still limited ( Lindsay and Dubey, 2020 ). Nevertheless, there is initial evidence that this way of transmission is also efficient in the ovine and caprine hosts ( de Oliveira Junior et al, 2020 ; Feitosa et al, 2021 ; González-Warleta et al, 2018 ; Pereira et al, 2021 ; Sánchez-Sánchez et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%